2003
DOI: 10.1016/s0002-9270(03)00014-5
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent and on-Demand Use of Proton Pump Inhibitors in The Management of Symptomatic Gastroesophageal Reflux Disease

Abstract: The epidemic of gastroesophageal reflux disease (GERD) in industrialized nations is currently spreading to less-developed ones, with more than half of the patients having symptomatic or mild erosive GERD. The long-term management of GERD has been dominated by daily maintenance treatment with proton pump inhibitors (PPI) to prevent relapse. It is common, however, for many patients with mild disease and infrequent symptom relapses to use a PPI only when symptoms demand. Patients with symptomatic or mild erosive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…A continuous use of PPIs is not necessary in many patients [8]. In a proportion of patients (60%) with mild symptoms of GERD, several studies have shown that on-demand or intermittent therapy with PPIs is efficacious [40]. On-demand therapy is a patient-centered approach to GERD and a cost-effective one when PPIs are used [41].…”
Section: Optimizing Therapy Of Gerdmentioning
confidence: 99%
“…A continuous use of PPIs is not necessary in many patients [8]. In a proportion of patients (60%) with mild symptoms of GERD, several studies have shown that on-demand or intermittent therapy with PPIs is efficacious [40]. On-demand therapy is a patient-centered approach to GERD and a cost-effective one when PPIs are used [41].…”
Section: Optimizing Therapy Of Gerdmentioning
confidence: 99%
“…Research demonstrates that up to 80% of presumed GERD patients on continuous PPI treatment can be stepped-down to less intensive therapy, such as dosage reduction, on-demand or intermittent therapy [11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Besides healing of the esophagus, the aim of a therapeutic intervention for GERD should not only be to reach rapid, but also sustained symptom relief. Evaluations of the phase after initial treatment are done in the context of long-term treatment, e.g., continuous [13,14,15] or on-demand treatment [16, 17]. These studies often define a relapse as the recurrence of mucosal damage determined in an endoscopy at a predefined time point [29, 30] or when symptoms seem to suggest a relapse after 3 consecutive days of GERD symptoms [14, 31].…”
Section: Discussionmentioning
confidence: 99%
“…This results in a high rate of relapses after successful treatment, when the intake of medication is stopped. Relapses occur in about 70% of all patients within 6 months after initial medication [12,] resulting in the necessity of long-term (maintenance) treatment which is often given as continuous treatment [13,14,15] or as on-demand treatment [16, 17]. …”
Section: Introductionmentioning
confidence: 99%